KONTROL KINEMATIKA DARI ALAT BANTU MOBILITAS BAGI PENYANDANG DISABILITAS MENGGUNAKAN LOGIKA FUZZY - Mauludi (Ben Gurion), M.Iqbal
Mobility aids for people with disabilities are still rarely used in Indonesia because the price is quite expensive. In this final project, mobility aids are designed using a fuzzy approach with a relatively affordable and safe price range. Fuzzy logic is a form of artificial intelligence that is used to make decisions like humans. Fuzzy logic will be used to regulate the speed of mobility aids based on information provided by ultrasonic sensor. From the experiment obtained output distance data from ultrasonic sensor and another output data in the form of pulse width modulation (PWM) that can be converted into the mobility aid velocity. The experimental results using a fuzzy approximation will be compared with theoretical fuzzy logic calculations. The error value is about 0.2% to 1.7%, indicate that the application of fuzzy logic can be developed as a mobility aid. Application of fuzzy logic on wheelchair has been successful after modifying fuzzy logic input parameters.